Dynamics of C/N and nutrients in Oxisol soils treated with swine digestate. - BERGIER, I. (2016)
We present C/N and nutrient soil data of 6 integrated swine-cattle farms in São Gabriel do Oeste that have been applying effluent to pasture over different time spans and variable effluent doses. The results are discussed under the light of effluent application, soil depth and time spans of effluent application.